2007
DOI: 10.1016/j.freeradbiomed.2006.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione protects cells against arsenite-induced toxicity

Abstract: To understand the role of glutathione (GSH) in the protection of cells from arsenite toxicity, we studied the mechanism of apoptotic cell death in cells genetically unable to synthesize GSH (GCS-2 cells). Arsenite stimulated an increase in protein ubiquitination in GCS-2 cells while the wild type cells were unaffected. Arsenite treatment increased lipid peroxidation and induced ubiquitination of molecular chaperone Hsp90 and impaired its ability to bind cochaperone p50 and client proteins Plk-1 and Cdk-4 in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…Using GSH-deficient GCS-2 cells, we have previously demonstrated that arsenite induces ubiquitination and apoptotic cell death [cytochrome C leakage and DNA fragmentation; Habib et al, 2007] and that p53 regulates Hsp90β during arsenite-induced cytotoxicity [Habib et al, 2009]. In the current study, we show that arsenite down-regulates Akt and c-Fos by ubiquitination, decreases AP-1 activity and causes cell cycle dysregulation and apoptotic cell death.…”
Section: Introductionsupporting
confidence: 57%
“…Using GSH-deficient GCS-2 cells, we have previously demonstrated that arsenite induces ubiquitination and apoptotic cell death [cytochrome C leakage and DNA fragmentation; Habib et al, 2007] and that p53 regulates Hsp90β during arsenite-induced cytotoxicity [Habib et al, 2009]. In the current study, we show that arsenite down-regulates Akt and c-Fos by ubiquitination, decreases AP-1 activity and causes cell cycle dysregulation and apoptotic cell death.…”
Section: Introductionsupporting
confidence: 57%
“…In cell lines with intrinsic low glutathione content, arsenic markedly induced lipid peroxidation assessed as malondialdehyde levels compared to cells with normal glutathione content; this lipid damage was prevented by pretreatment with glutathione or its precursor [Habib et al, 2007]. In another study, reduced levels of glutathi- Environmental and Molecular Mutagenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Conse-quently, exposure to arsenic compounds leads to increased levels of oxidative lesions in DNA, especially 8-hydroxy-2 0 -deoxyguanosine, products of lipid peroxidation, and protein carbonyls [Wanibuchi et al, 1997;Matsui et al, 1999;Yamanaka et al, 2001;Bau et al, 2002;Eblin et al, 2006;Wang et al, 2007]. An important feature of arsenic-induced toxic effects is related to its high ability of reacting with protein and nonprotein thiol groups resulting in an alteration of critical cellular pathways [Valko et al, 2006;Habib et al, 2007]. Additionally, it has been shown that reduced glutathione content is inversely correlated with sensitivity of cells to arsenic exposure [Nakagawa et al, 2002;Habib et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4a demonstrates that GSH levels in the 10 −3 , 10 −2 , 10 −1 and 1 mg/l PtNP-treated L6 cells increased significantly without concentration dependency compared with that of the untreated control cells ( ** p<0.01). Such elevated GSH levels are expected to act on ROS directly, thereby protecting the cells from oxidative stress [44,45]. The level of intracellular GSH induced by 10 mg/l was similar to that of the control cells.…”
Section: Cellular Gsh and Gssg Content Affected By Ptnpsmentioning
confidence: 66%